“What do they mean?” a systematic review on the interpretation, usage and acceptability of “they” - Batista da Costa, Mafalda; Tenenbaum, Harriet R.; Grandison, Alexandra (Frontiers in Psychology, 2024)
The rise of feminist and LGBTQ+ movements paved the way for many equality reforms. These include language reforms, which facilitate inclusion of multiple groups in society. For example, the shift from the generic “he” to “he or she” and “they” allows for the inclusion of women, transgender, and non-binary individuals in many narratives. For this reason, many institutions worldwide encourage neutral language. It remains unclear how individuals interpret neutral language. One case of neutral language is the pronoun “they”, which has been assigned multiple definitions from the 1970s to 2022. We examine how the pronoun “they” has been interpreted, used, and accepted over time. We discuss trends in the findings and make suggestions for future research directions, including the need for better methods to investigate pronouns and clarification on what the focus of neutral language should be. This timely commentary has implications for action on equality, diversity, and inclusion.